Age-growth models for tilapia Oreochromis aureus (Perciformes, Cichlidae) of the Infiernillo reservoir, Mexico and reproductive behaviour - Jiménez Badillo, Lourdes (2006)
In presence of a decrease in the catch from Infiernillo reservoir, Michoacán-Guerrero, México, ageand growth of tilapia Oreochromis aureus (Steindachner 1864) were estimated, as indispensable attributes forfishery management. Evaluations included scales and opercular bones readings and length frequency analysis.The population structure was determined too. Due to the great variation of tilapia individual growth and withthe objective to have reliable growth estimations, linearized, non-parametric and non-linear methods were usedand their applicability discussed. Comparison of ages determined from these methods revealed that opercularbones readings had advantages over scales. Reproduction and competition for space and food were consideredas responsible factors for ring-formation on tilapia hard structures. The non-linear method was considered thebest for modelling populations highly variable, which is characteristic of tilapia and tropical fish with multiplespawns. The growth parameters estimated were L∞ = 479 mm, K = 0.46/yr, to = -0.055 yr. The tilapia populationin Infiernillo reservoir is dominated by juveniles less than 1.5 years old. The fishery activity is affectingthe tilapia population growth because are caught when they have not yet spawned. Therefore, this fishery is inurgent need of regulation. Increasing the mesh size of the gill nets might contribute to protect the reproductivepotential of the stock.